Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/evo.13598
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 as a global genetic modifier for male genital morphology inDrosophila melanogaster

Abstract: The molecular chaperone protein HSP90 has been proposed to modulate genotype-phenotype relationship in a broad range of organisms. We explore the proposed genetic modifier effect of HSP90 through a genomewide analysis. Here, we show that HSP90 functions as a genetic modifier of genital morphology in Drosophila melanogaster. We identified a large number of single-nucleotide polymorphisms (SNPs) with an HSP90-dependent effect by using genome wide association analysis. We classified the SNPs into the ones under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We found that E5 is expressed in the posterior lobe, the ventral portion of the EVL (see additional samples online), and the phallus. E5 is a homeodomain transcription factor (Dalton et al 1989) associated with variation in posterior lobe morphology among Drosophila melanogaster populations (Takahashi et al 2018). We also found that brother of odd with entrails limited ( bowl ) is expressed in the posterior lobe at 48 hr APF, as well as other tissues throughout the terminalia (Figure 2C-E).…”
Section: Resultsmentioning
confidence: 99%
“…We found that E5 is expressed in the posterior lobe, the ventral portion of the EVL (see additional samples online), and the phallus. E5 is a homeodomain transcription factor (Dalton et al 1989) associated with variation in posterior lobe morphology among Drosophila melanogaster populations (Takahashi et al 2018). We also found that brother of odd with entrails limited ( bowl ) is expressed in the posterior lobe at 48 hr APF, as well as other tissues throughout the terminalia (Figure 2C-E).…”
Section: Resultsmentioning
confidence: 99%
“…Our results support the view that the role of proteostasis is but one part of an integrated "quality system (QS)" 20 that is responsive to genetics, development, aging, and the environment to continually reshape sequence-to-function-to-structure relationships driving protein fold dynamics contributing to health and disease 1,17,20,34,110 that is not captured in static structures 21,34 . As it is well established by the pioneering efforts of Lindquist and others 68,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127] that Hsp90 serves as a capacitor for natural selection and evolution, SCV principled relationships now suggest that Hsp90's role in capacitance management of variation occurs on a residue-by-residue basis-but as a collective. The response of Hsp90 family members to ATPase inhibitors suggests their role in cellular QS 20 is acutely tuned by the use of different cochaperone partners to facilitate fitness 6,14,15,44,128 .…”
Section: Discussionmentioning
confidence: 99%
“…2011; Masly and Kamimura 2014; Frazee and Masly 2015; Takahara and Takahashi 2015; Takahashi et al. 2018; Tanaka et al. 2018).…”
Section: Methodsmentioning
confidence: 99%